The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/21645515.2016.1214347
|View full text |Cite
|
Sign up to set email alerts
|

Analyzed immunogenicity of fractional doses of Sabin-inactivated poliovirus vaccine (sIPV) with intradermal delivery in rats

Abstract: The live-attenuated oral polio vaccine (OPV) will be no longer used when wild poliovirus (WPV) eliminating in worldwide, according to GPEI (the Global Polio Eradication Initiative) Reports. It is planning to replace OPV by Sabin-based inactivated poliovirus vaccine (sIPV) in developing countries, with purpose of reducing of the economic burden and maintaining of the appropriate antibody levels in population. It studied serial fractional doses immunized by intradermal injection (ID) in rats, to reduce consume o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Induction of sufficient immune responses by ID delivery of the fractional dose of an existing formulation was encouraging. Since reformulation of existing vaccine needs expensive processes, the present results may facilitate the development of ID delivery as an alternative to SC/IM vaccination.…”
Section: Discussionmentioning
confidence: 91%
“…Induction of sufficient immune responses by ID delivery of the fractional dose of an existing formulation was encouraging. Since reformulation of existing vaccine needs expensive processes, the present results may facilitate the development of ID delivery as an alternative to SC/IM vaccination.…”
Section: Discussionmentioning
confidence: 91%
“…According to the WHO, the ID route of delivery could reduce the required antigen by 1/5 of the full vaccine . In our previous study, we found that a 1/5 fractional dose could be used by ID injection to prevent poliovirus infection. However, ID delivery might not be suitable for KML05.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody determination was done by the standard microneutralization technique using Vero cells. The definition of seroconversion rate was consistent with our previous study . Quality‐control requirements were as follows: the serum was heated for half an hour at 56℃ and tested in six steps by twofold dilutions, with a final dilution of 1:320.…”
Section: Methodsmentioning
confidence: 99%
“…ID delivery has been proposed as a means to reduce the dose required for vaccination, and it has been shown in several phase 3 trials in infants and adults to be a promising option to dose-spare by 60–80%, despite certain limitations(e.g., dose regimen and age). 10-13 For sIPV, our laboratory conducted pioneering ID tests in rats 14 and found out that the dose could be reduced by 80%, thus, further clinical trials are in preparation. In parallel with ID tests for sIPV, we also seek to determine optimal adjuvants for sIPV.…”
Section: Introductionmentioning
confidence: 99%